(3GdMeGjI GdLfGFjI ddHjFI GdHMQjI (B: s (3OQGSI ebGQfI (B/ s - (3eMeO GMeO efTGhi eMeOs; (3eGehf eMeO SdGeg s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2005)
(3Gf Gddg JYGdi Ndb Gdchf HMceI HGdZI hai HjFI eJhGRfI JJaGYd YfGUQgG ajeG HjfgG HMjK JTcd GdHjFI GdGUdM ddGfSGfjI GdJi JYJeO YdjgG ai MjGJgG hJbOegG GYJeGOG eWdbGhefP HOA GdNdjbI Ydi GdGQV hGdMjGI eQJHWI HGdeGAMjK Gfg YUH Jdc GdMjGI hGge echfGJgG ShGA GcGf YPHG aQGJG Ge edMG GLGLGaGdeGA GdeGdM jMed ef GdUaGJ eG jecfg ef GYGdI GdMjGI Ydi SWM GdGQVMjK Gfg jeKd HjFI GdcKjQ ef GdeNdhbGJ hGdcGFfGJ GdMjI (B(1) (3hbO GTGQ GdbQGf GdcQje Gdi GgejI Jdc GdHjFI Hbhdg (B((3hgh GdPi SNQ GdHMQ dJGcdhG efg dMeG WQjG hJSJNQLhG efg MdjI JdHShfgG hJQi Gdadc ehGNQ ajg(B) (2) (3hGjVG Hbhdg JYGdi (B((3GMd dce UjO GdHMQ hWYGeg eJGYG dce hddSjGQI(B) (3) (3hfXQG dgPg GdGgejI GdcHjQI LYd Gddg GdeGA MbG TGFYG Hjf GdHTQ LejYG Ohf GMJcGQ Gh GaSGOs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2005s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B462-493s
Keywords: (3GdbGfhf GdLfGFjs; (3GdHMQs; (3GdJdhK YHQ GdMOhOs; (3GdHjFI GdHMQjIs; (3GdJdhK GdHMQjs; (3JdhjK GdHjFIs; (3GdbGfhf GdHjFjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs